Preparation of nanocrystalline ferroelectric CaBi2TaO9 by citrate gel method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A gel was formed when an aqueous solution of CaCl2, BiCl3, TaF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600degreesC yielded the nano-crystallites of ternary oxide, CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) are also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 40 nm. The room temperature dielectric constant was found to be 90. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Bismuth; diffraction; Electron microscopy

Rapid hydrothermal synthesis route for nanocrystalline SrZrO3 using reactive precursors - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Bapat, Malini S. (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Synthesis of nanocrystalline, orthorhombic (space group Pnma) SrZrO3 was achieved using appropriate molar proportions of nitrate salts of strontium and zirconium as precursors. Formation of SrZrO3 (SZ) was facilitated hydrothermally in time period as less as half-an-hour, in aqueous medium with alkaline pH as confirmed by XRD. Sample characterization was performed by FT-IR spectroscopy; powder XRD, SEM, TEM and DSC. The results have been explained by proposing a suitable reaction mechanism based on the step-wise analysis of the reaction intermediates using FT-IR as well as XRD. A double cation hydroxide composite formation is anticipated that under hydrothermal conditions results in the formation of SrZrO3. Morphology of the samples was determined with the help of SEM and TEM. The particle size distribution as seen from the TEM micrograph lies in the range of 15-25 nm. Heats of reaction for different decomposition steps were obtained by DSC. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Crystallization; diffraction; Electron microscopy; infrared spectroscopy

Nutty carbon: morphology replicating hard carbon from walnut shell for na ion battery anode - Wahid, M.; Gawli, Y.; Puthusseri, D.; Kumar, A.; Shelke, M. V.; Ogale, S. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-7/acsomega.7b00633/20170713/images/medium/ao-2017-00633k_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Efficient Na ion intercalation/deintercalation in the semigraphitic lattice of a hard carbon derived from the walnut shell is demonstrated. High-temperature (1000 °C) pyrolysis of walnut shells under an inert atmosphere yields a hard carbon with a low surface area (59 m2 g–1) and a large interplanar c axis separation of 0.39–0.36 nm as compared to 0.32 nm for graphite, suitable for Na ion intercalation/deintercalation. A stable reversible capacity of 257 mAh g–1 is observed at a current density of 50 mA g–1 for such nutshell-derived carbon (NDC) with an impressive rate performance. No loss of electrochemical performance is observed for high current cycling (100 mA g–1 → 2 A g–1 → 100 mA g–1). Additionally, the NDC shows remarkably stable electrochemical performance up to 300 charge–discharge cycles at 100 mA g–1 with a minimal drop in capacity.
Keywords: Batteries; Biological and Medicinal chemistry; Biological materials; diffraction; Electric Properties; Electrode-electrolyte interface; spectra; Surface structure; Thermal properties